CHARACTERIZATION OF NEWCASTLE DISEASE ANTIBODY RESPONSE AND SOME RELATED PERFORMANCE INDICATORS OF TWO LOCAL SAUDI CHICKEN LINES AND TWO CROSS LINES DURING THE REARING PERIOD - M. S. El Sayed; A. S. Ahmed; Y. M. Alyousef (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to assess antibody response against Newcastle disease (ND) vaccination of one hundred and sixty female chicks represented equally two local Saudi chicken lines Hajar 1 and Hajar 2, In addition to crossbreed HiH1, and HiH2 lines during the rearing period from four to 16 wk of age. Body weight (BW), hemoglobin concentration (Hb) and hematocrit percent (Ht) were evaluated as accompany performance indicators.  The chicks were housed in a cage housing system and fed commercial rations. Birds were received identical vaccination program. Body weights were recorded for all birds individually at 4,8,12, and 16 weeks of age. Blood samples were collected in both heparinized and plain tubes at 4, 8, 12, and 16 weeks of age. Circular micro-capillary tube reader was used to evaluate Ht values. Haemoglobin concentrations were determined through cyanomet hemoglobin method. ND antibody titers were assayed using Enzyme-Linked Immunosorbent Assay (ELISA) kit. The two crossbreed lines showed superior body weight, especially starting from the 8th week of age while HiH2 and Hajar2 lines showed higher ND titers than Hajar1 and HiH1 lines. Hb values were significantly higher for Hajar1 and Hajar2 lines. Ht did not show differences among the chicken lines at any measuring point. The diverse genetic background of the birds is a key role in shaping the cross line birds' immune capacity against ND. The superior body weight of the cross lines is not necessarily an indicator of their immune response tendency.
Keywords: Immune response; ELISA; Saudi chicken lines; crossing; ND